A Pilot Study on the Impact of ICT and New Media on Society and Culture (International Journal of Innovative Research in Engineering & Management, 2021)
Communication is vital for human existence. In all social  structures and cultural practices, communication is very  important. The development of culture and society is greatly  influenced by how individuals interact, interpret information, and  communicate with one another. The last few years have seen  significant development in the field of Information and  Communication Systems. These systems have changed the way  people communicated a few years back. It is not only the  communication pattern but these systems have immense capacity  to create, capture, compute and distort information just in a matter  of seconds. This has posed a big challenge to existing society and  culture. As with every change in the way we consume and  communicate information, there is a new struggle over meaning,  significance, knowledge, and power. Old rules, orders, and beliefs cannot be applied perfectly under the new regime and thus  formations of power, significance, and meaning of knowledge are  all under threat from these changes. This work is an attempt to  study these new means of information and communication  systems in terms of their impact on our society and culture. The  study is concentrated on understanding how ICT, New media, and  Internet are playing their roles in our cultural formation and  adaptation of society. The concluding part of this work is to see  the role of these technologies in the current scenario and draw  conclusions from them.
Keywords: ICT; New Media; Society; Culture; Positive role; Negative role